DISASTER MITIGATION GOVERNANCE TO MAINTAIN ENVIRONMENTAL SUSTAINABILITY BASED ON CO - SERVICE BY NON GOVERNMENTAL ORGANISATIONS: A STUDY OF THE MUHAMMADIYAH DISASTER MANAGEMENT CENTRE (MDMC) IN WATULIMO SUB DISTRICT, INDONESIA (INTERNATIONAL SEMINAR, 2025)
Environmental sustainability in disaster-prone regions requires measurable community resilience, and this study quantitatively examines the role of the Muhammadiyah Disaster Management Centre in supporting environmental sustainability through disaster mitigation in Watulimo District. A survey method with a structured questionnaire was distributed to community members, volunteers, and local stakeholders, producing 120 valid responses. The instrument measured perceptions of environmental awareness, mitigation readiness, and the effectiveness of MDMC interventions using a five-point Likert scale. Data were analyzed using descriptive statistics and correlation tests to identify the relationship between MDMC activities and indicators of environmental sustainability. The results show that MDMC programs significantly contribute to environmental sustainability, with high mean scores in environmental education (M=4.21), community preparedness (M=4.08), and ecological risk reduction (M=4.15). Correlation analysis indicates a positive and significant relationship (r=0.62, p